Transformation and removal of riverine dissolved organic matter in Baltic Sea estuaries - Asmala, Eero (Suomen ympäristökeskus, 2014)
The pool of riverine dissolved organic matter (DOM) results from integration of complex catchment processes, and links the terrestrial and coastal systems by transporting organic matter from watersheds to estuaries. In this thesis, field samplings and laboratory experiments were combined to assess the spatio-temporal variation in riverine DOM quantity and quality in three Finnish estuaries discharging to the Baltic Sea. Also, the biogeochemical transformation and removal processes influencing the composition of the DOM pool were studied. Large-scale catchment characteristics were linked to the properties of the riverine DOM. Throughout the work the DOM quality was assessed using multiple analytical approaches: C/N stoichiometry, colored DOM (CDOM) absorption, CDOM fluorescence, molecular weight and iron content. Estuarine DOM was subjected to heterotrophic degradation in factorial experiments to quantify the role of salinity, inorganic nutrients and predegradation to DOM bioavailability. Additionally salt-induced flocculation of DOM was studied by combining field samplings, laboratory experiments and modeling. The selected three study catchments differed markedly in their land-use, and these differences were reflected on the riverine DOM quantity and quality. The experiments provided evidence that increasing proportion of forests and peatlands were linked to the increase of carbon loading from the catchment, and to decreases in the subsequent quantities of bioavailable dissolved organic carbon (DOC) and bacterial growth efficiencies (BGE). A higher proportion of agricultural land in the catchment indicated an increase of the amount and bioavailability of dissolved organic nitrogen (DON) in the DOM pool. A larger proportion of lakes in the catchments were related to decreased bioavailable DON. Replete inorganic nutrients did not influence the DOM bioavailability, although did increase BGE on average from 11 to 40%. Increasing predegradation, i.e. DOM subjected to heterotrophic degradation for varying times before ...